PERMAINAN TRADISIONAL DHAKONAN MENCEGAH PROGRESIFITAS TINGKAT DEMENSIA PADA LANSIA - Mita Nur Lathifah; Joni Haryanto; Rista Fauziningtyas (Fakultas Ilmu Kesehatan, 2017)
One of the elderly problem is dementia, which can interfere daily activity. One of the safetreatment for elderly with dementia is reminiscence therapy with dhakonan traditional games. Thepurpose of this study is explain the effect of dhakonan traditional games on dementia level in theelderly.The design of this study was quasy-experiment design. The population was elderly withdementia in Desa Wedoro Kecamatan Waru Kabupaten Sidoarjo. The total sample were 20respondents who appropriate to inclusion criteria. The sampling was simple random sampling. Theindependent variable was dhakonan traditional games, the dependent variable were cognitivefunction, depression, and dementia level. Data were collected using quissionaires of Mini MentalState Examination (MMSE), Geriatric Depression Scale (GDS), dan Functional AssessmentStaging Tool (FAST). Data analysis were Wilcoxon Sign Rank Test and Mann Whitney Test withsignificance level of α<0,05.Based on Wilcoxon Sign Rank Test found that p<0,05 for cognitive function, depression level,and dementia level in treatment group (cognitive function, p= 0,005; depression level, p= 0,005;dementia level, p= 0,014), it means the dhakonan traditional games had an effect to the dementialevel in the elderly.The conclusions of this study was the dhakonan traditional games significantly increasedcognitive function, decreased depression level and prevent progressifity of dementia level. Thefuture studies can add the respondents and behavioral changes in elderly with dementia.